A Penerapan Program Kanzul Mall Dalam Membangun Kesadaran Spiritual dan Silaturahim antara Guru, Orang tua, dan Siswa di MTs Madrasatul Qur’an Tebuireng Jombang: Penerapan Program Kanzul Mall Dalam Membangun Kesadaran Spiritual dan Silaturahim antara Guru, Orang tua, dan Siswa di MTs Madrasatul Qur’an Tebuireng Jombang - Masita, Azza; Syamsuddin (Al Tadib : Jurnal Ilmu Pendidikan, 2024)
Abstract: Kindness can be done in any way such as smiling, giving alms, saying good things and so on. This can be made a habit of anywhere and anytime, as has been done by MTs Madrasatul Qur'an Tebuireng Jombang, namely the implementation of the alms program, namely Kanzul Maal (Charity) where alms are made by teachers and guardians of students whose funds will later be given to students in need. Not only students but all madrasa families both internally and externally outside the scope of the madrasa (natural disasters). Based on this background, this researcher aims to find out: 1. What is the form of the kanzul maal (charity) program at MTs Madrasatul Qur'an Tebuireng Jombang, 2. How is the implementation of the Kanzul Maal (charity) program in building spiritual awareness and friendship between teachers, parents , and Students at MTs Madrasatul Qur'an Teb, uireng Jombang., 3. What are the inhibiting factors and supporting factors for implementing the Kanzul Maal (Charity) program in Building Spiritual Awareness and Friendship between Teachers, Parents, and Students at MTs Madrasatul Qur' an Teb, uireng Jombang. The term qualitative is the use of a method that is considered appropriate in this study, the type chosen is descriptive qualitative as well. The results of the study show that the application of the Kanzul Maal (Sedaqah) Program in Building Spiritual Awareness and Friendship between Teachers, Parents, and Students at MTs Madrasatul Qur'an Teb, uireng Jombang shows that: 1. The form of the kanzul maal (charity) program is a program alms or charities carried out by the madrasa which later funds will be donated to students in need and to all madrasah families who are in need and externally such as disasters and other natural disasters. 2. This kanzul maal (charity) program is a place to help each other and to realize that everything one has is temporary and with that the ties of friendship based on affection will build and become tighter regardless of one's background, only giving up everything to Allah SWT. 3. The supporting factors of this program are the support from parents and teachers as well as an information system that can be reached by all parties involved, while the inhibiting factors of this program have not existed so far, it's just that this program needs habituation and it's all not a problem.